Pre-travel advice at a crossroad: Medical preparedness of travellers to South and Southeast-Asia - The Hamburg Airport Survey. Issue 18 (July 2017) - Rolling, Thierry; Mühlenpfordt, Melina; Addo, Marylyn M.; Cramer, Jakob P.; Vinnemeier, Christof D.
Abstract: Background: Specific travel-related recommendations exist for the prevention or self-treatment of infectious diseases contracted by travellers to the tropics. In the current study, we assessed the medical preparedness per these recommendations, focusing on whether travellers carried antidiarrheal and antimalarial medication with them stratified by type of pre-travel advice. Methods: We surveyed travellers departing from Hamburg International Airport to South or Southeast Asia, using a questionnaire on demographic, medical and travel characteristics. Results: 975 travellers were analysed – the majority (817, 83%) being tourists. A large proportion packed any antidiarrheal medication (612, 63%) – most frequently loperamide (440, 72%). Only 176 of 928 (19%) travellers to destinations with low-to medium risk for malaria packed a recommended antimalarial medication. The majority (162, 17%) of them carried antimalarials as stand-by emergency treatment (SBET). 468 (48%) travellers had a pre-travel medical consultation. This lead to higher odds of carrying SBET– with the highest odds associated with a consultation at a travel medicine specialist (OR 7.83 compared to no consultation). Conclusions: Attending a travel medicine specialist was associated with better adherence to current recommendations concerning the carriage of stand-by emergency treatment of malaria. However, the proportion of travellers seeking pre-travel health advice was overall low in our population. Promoting pre-travel consultations may, therefore, lead to higher adherence to the current recommendations in travel medicine